2017
DOI: 10.1111/jcpe.12794
|View full text |Cite
|
Sign up to set email alerts
|

Exercise attenuates alveolar bone loss and anxiety‐like behaviour in rats with periodontitis

Abstract: Exercise decreased anxiety behaviour, inflammatory proteins expression and bone loss in rats with PD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 79 publications
2
25
1
Order By: Relevance
“…The placement of ligatures around teeth to initiate periodontal attachment loss has been used in various types of animals. The rat ligature model is widely used (Andrade et al., ; de Molon et al., ) because they are relatively simple, of low cost and the biological response is physiologically similar to that of humans (Klausen, ; Listgarten, ). In the rat, loss of attachment occurs predictably in a 7‐day period (de Almeida et al., ; Graves et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…The placement of ligatures around teeth to initiate periodontal attachment loss has been used in various types of animals. The rat ligature model is widely used (Andrade et al., ; de Molon et al., ) because they are relatively simple, of low cost and the biological response is physiologically similar to that of humans (Klausen, ; Listgarten, ). In the rat, loss of attachment occurs predictably in a 7‐day period (de Almeida et al., ; Graves et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Also according to Andrade et al (2017) 8 , attenuation of alveolar bone loss and loss of epithelial insertion in trained animals may be related to improved inflammatory profile, as there was an increase in the IL-10 expression (Interleukin-10) and a decrease in TNF-α (tumor necrosis factor-α) in the adjacent tissues of these animals. Besides, the decrease in the TNF-α/IL-10 ratio observed in animals with induced periodontitis undergoing training confirms the improvement in the inflammatory state, as the increase in this ratio is indicative of more severe periodontitis.…”
Section: Discussionmentioning
confidence: 80%
“…When the osteoblast and osteocyte counts were evaluated, a significant decrease was found in the groups undergoing experimental periodontitis, but without any change when associated with physical exercise. Andrade et al (2017) 8 , evaluating animals trained with 1 hour/day swimming sessions for 8 weeks, also found that physical training attenuated alveolar bone loss and levels of loss of epithelial insertion of rats with PD. The distance from the cementoenamel junction to the alveolar bone crest assessed histologically was found to be lower in the group with PD and trained than in the untrained PD group, corroborating with our study regarding the protective effect of physical exercise against the progression of PD.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations